INDONESIA AND THEIR RADICAL ORGANIZATIONS CORRELATION TO THE INDONESIAN UNITY FUTURE - Albiansyah Albiansyah (STAIN Sultan Abdurrahman Kepulauan Riau, 2020)
ABSTRACT This paper provides an overview about the activities of radical Indonesian organizations and their relation to Indonesian Unity's Future. This study’s objective is to show the praxis and philosophy of radicalism are a big risk to Indonesia's future. This study will be carried out by analyzing some information or data and phenomena in press and kinds of literature in terms of radicalize organizations. This study is literature-based research in Indonesia from some books, journals, and hypotheses about radicalism. All in all, this paper calls on all facets about government, academic institutions, and people to mitigate the radicalism motion in Indonesian. Keywords: Islam, Radical, Violence